Analisis Kinerja Empu Dalam Melaksanakan Prosedur Incoming Internasional Cargo Human Remains di Pt Angkasa Pura Logistik Cabang Bandar Udara Internasional Ahmad Yani Semarang - Muhammad Ridho Feby Firnanda; Djoko Widagdo (Pusat Riset dan Inovasi Nasional, 2024)
The ACX (Aircraft Cargo Expedition) Unit is a Logistics unit at Ahmad Yani Airport in Semarang which is overseen by Angkasa Pura Logistik. This unit is located at the very back of the airport. This unit has a role, namely as a place for expeditions who wish to send large or small cargo using domestic and international aircraft. This research uses qualitative methods and uses data collection techniques, namely observation, interviews, and documentation and uses data analysis techniques in the form of data collection, data reduction, and drawing conclusions. The research results showed that the EMPU (Aircraft Cargo Expedition) officers had carried out their work according to the SOP (Standard Operational Procedure) from the results of their performance during the Incoming International Human Remain process at Ahmad Yani Airport in Semarang, however they were still hampered by information when collecting cargo and documents. required. To solve the problem, what must be done is that the EMPU (Aircraft Cargo Expedition) must provide information from the start about what requirements and documents are needed when the pick-up occurs.